Helbig, Adriana. 2014. Hip Hop Ukraine: Music, Race, and African Migration. Bloomington, IN: Indiana University Press. - Holt, Kevin (Current Musicology, 2014)
The underpinning principles of Hip Hop Ukraine: Music, Race, and African Migration conform to broader trends within hip hop studies. Scholars are increasingly breaking with the traditional approaches, which centralized (African?)Americanness as a governing frame, in favor for approaches that emphasize the global reaches of the imagined hip hop community, taking into account the various ways that non–American hip hoppers negotiate meaning and authenticity through the subculture in their respective locales. In this way, scholars are actively interrogating the notion that American hip hop represents a universal base for hip hop studies. With Hip Hop Ukraine, Adriana L. Helbig goes a step further than many of her contemporaries by presenting a complicated, multilayered negotiation of identity, which, as she observes, places American, African, African–American, black, Ukrainian, Ukrainian–American, white, and European identities in dynamic discourse. In order to present this delicate intersectional arrangement of race, ethnicity, and nationality, Helbig offers an historical overview of the ways in which those tenets of identity have shifted throughout the twentieth century, particularly in relationship to socialist and post–socialist regimes in Ukraine. She outlines various overlapping networks of migration between West Africa, Eastern Europe, and the United States of America as a means of asserting an active exchange of subcultural particularity and meaning between the three, thereby challenging the concept of a unidirectional dissemination of hip hop music culture spreading from the U.S. to the rest of the world. The result is a stunningly intricate chronicle, which sets the foundation, not just for Helbig’s discussion of hip hop in Ukraine, but also for future research on popular music, race, ethnicity and identity more generally. It should be noted, however, that this project necessitates an emphasis on histories that long pre–date the formation of hip hop, American or otherwise, which means that, despite the name of this book, hip hop does not enter as a central focus until the latter chapters.